2018
DOI: 10.5902/1980509833366
|View full text |Cite
|
Sign up to set email alerts
|

Influência Da Forma E Posição Da Encosta Nas Características Do Solo E Na Regeneração Natural Em Áreas De Pastagem Abandonadas

Abstract: O objetivo desse trabalho foi avaliar a influência do relevo nas características químicas e físico-hídricas do solo e na regeneração natural, em áreas de pastagens abandonadas. Para o estudo foram consideradas oito áreas de relevo movimentado no município de Itaboraí-RJ, em cada uma das áreas foram selecionadas duas topossequências divididas em terços superior, médio e inferior, contemplando as pedoformas côncavas e convexas. Foram instaladas duas parcelas (20 m x10 m) em cada terço, uma para cada pedoforma, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the study conducted by Teixeira (2009), assessing the phytosociology and floristic aspects of the arboreal component in toposequenc, there were reported that the species revealed specific characteristics in the relief and showed a preference for different habitats. Silva (2011), explained that variations in the physical and chemical properties of the soil at different locations on the slope directly influence the vegetation growth. Besides, he also highlighted that the Brazilian soils have distinctly marked features of high acidity and low fertility, and when the relief factor is considered, as these involve sloping regions, the bases are even more easily removed.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Teixeira (2009), assessing the phytosociology and floristic aspects of the arboreal component in toposequenc, there were reported that the species revealed specific characteristics in the relief and showed a preference for different habitats. Silva (2011), explained that variations in the physical and chemical properties of the soil at different locations on the slope directly influence the vegetation growth. Besides, he also highlighted that the Brazilian soils have distinctly marked features of high acidity and low fertility, and when the relief factor is considered, as these involve sloping regions, the bases are even more easily removed.…”
Section: Discussionmentioning
confidence: 99%
“…This species can be indicated for recovery of degraded areas, mainly by its high adaptation in mining areas (Jesus et al, 2016). On the other hand, the high infestation of herbaceous species may negatively influence natural regeneration, leading to resistance in the succession process (Rodrigues et al, 2010;Silva et al, 2018).…”
Section: /10mentioning
confidence: 99%
“…The lower soil cover percentage in the mechanical treatment after 19 months, resulting of the slow-paced growth of the tree species (Figure 2 and 3), suggests a reflection. Presence of weeds is one of the limiting factors in the establishment and survival of native tree species (Ruwanza et al, 2013;Silva et al, 2018). In highly infested conditions, the employment of techniques that are not effective may jeopardize the restoration area success, in addition to raise the project cost.…”
Section: -10mentioning
confidence: 99%
“…These species are widely adapted to prevailing over conditions of high sunlight radiation and temperature in the tropics (Zhong et al, 2018) and have an increased ability in capturing and converting resources as sunlight, water and nutrients (Haling et al, 2013). Thus, these grasses can harm the forest restoration success (Silva et al, 2018), becoming an important group of harmful weeds if not properly controlled.…”
Section: Introductionmentioning
confidence: 99%